Adjudication of disputes in the Icelandic Commonwealth (Ius Novum, 2020)
The Icelandic Commonwealth (ca. 930–1264) is a relatively well documented pre-state society based on chieftaincy. The Free Commonwealth institutional structure was based on a number of public assemblies (þing), which provided a meeting place for the local chieftains (goðar) and their followers recruited from the householders class (bændr). The assemblies had judicial functions and were often used to adjudicate legal disputes. The aim of this article is to reconstruct the assembly court proceedings using the extant private Old Icelandic lawbooks known as Grágás. In particular, special consideration is given to the case initiation process, the geographical, subject-matter and functional jurisdiction of various assembly courts, as well as to the formal means of proof, and the rules for convictions.
Keywords: Icelandic Commonwealth; assembly courts; court proceedings; Grágás